An Animal Model for Research on Wound Healing over Exposed Bone - Bradley, D. M.; Swaim, S. F.; Stuart, S.W. (Veterinary and Comparative Orthopaedics and Traumatology, 1998)
Many wounds such as degloving injuries, or dermal ulcerative processes may have exposed bone. This presents a problem in wound healing. Various procedures such as tissue flaps, skin expansion, skin grafts, or open wound healing may be used to treat wounds with exposed bone. The development of a healthy granulation tissue bed provides the supportive structural matrix and vasculature needed to promote wound healing over exposed bone. This is beneficial when flaps or expanded skin are used and is necessary if skin grafts or open wound healing are used for treatment. This paper describes an animal model and surgical technique that can be used in studying factors that might enhance wound healing over exposed bone. A technique is described whereby a rectangular defect with exposed bone is made over the second metatarsal bone of New Zealand white rabbits. Using subjective observations and objective planimetry, the rate of healing can be evaluated. The animal model and technique provide a means of evaluating effects of medications and bandages on the healing of wounds with exposed bone. The model could also be considered a model for wounds with delayed healing.This paper describes an animal model and surgical technique that can be used to study wound healing over exposed bone. The surgical technique involves the creation of a rectangular defect over the second metatarsal bone of New Zealand White rabbits, with removal of the overlying periosteum. Various topical medications and/or bandage materials can be evaluated as to their effects on the healing of wounds with exposed bone. Bilateral defects can be created, with the animal serving as its own control. Subjective and objective evaluations involving planimetry, histopathologic, biochemical, or immunohistochemical analyses of harvested tissues may be conducted.
Keywords: New Zealand white rabbits; wound healing; exposed bone; animal model; granulation tissue